USING THE IDEAS OF EASTERN THINKERS IN EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article highlights the importance of using the ideas of Eastern thinkers in providing economic education in preschool educational institutions.